Accelerated evolution of dim-light vision-related arrestin in deep-diving amniotes - Guo, Xin; Cui, Yimeng; Irwin, David M.; Liu, Yang (Frontiers in Ecology and Evolution, 2022)
Arrestins are key molecules involved in the signaling of light-sensation initiated by visual pigments in retinal photoreceptor cells. Vertebrate photoreceptor cells have two types of arrestins, rod arrestin, which is encoded by SAG and is expressed in both rods and cones, and cone arrestin, encoded by ARR3 in cones. The arrestins can bind to visual pigments, and thus regulate either dim-light vision via interactions with rhodopsin or bright-light vision by binding to cone visual pigments. After adapting to terrestrial life, several amniote lineages independently went back to the sea and evolved deep-diving habits. Interestingly, the rhodopsins in these species exhibit specialized phenotypes responding to rapidly changing dim-light environments. However, little is known about whether their rod arrestin also experienced adaptive evolution associated with rhodopsin. Here, we collected SAG coding sequences from > 250 amniote species, and examined changes in selective pressure experienced by the sequences from deep-diving taxa. Divergent patterns of evolution of SAG were observed in the penguin, pinniped and cetacean clades, suggesting possible co-adaptation with rhodopsin. After verifying pseudogenes, the same analyses were performed for cone arrestin (ARR3) in deep-diving species and only sequences from cetacean species, and not pinnipeds or penguins, have experienced changed selection pressure compared to other species. Taken together, this evidence for changes in selective pressures acting upon arrestin genes strengthens the suggestion that rapid dim-light adaptation for deep-diving amniotes require SAG, but not ARR3.